Integrated management of higher education institutions - Lopes, Rui Pedro (2016)
Higher education institutions have adopted education, research and cooperation as their main missions. Students, teachers and non-teaching staff articulate for lecturing, researching and developing projects and internships, according to the institution goals and strategy. Quality evaluation is of the utmost importance in the whole process, as it allows providing a competent and rigorous service as well as maintaining high level of attractiveness for additional funding, through cooperation and research projects. In this process, well supported management through rigorous information is necessary, providing a sound basis for reasoning and improvement. In this paper we present a custom made application, which we call JagPAD, to integrate, process and visualize information from several departments and sections, such as student records, human resources, scientific repository and others. This application is in use at the Polytechnic Institute of Bragança and constitutes a valuable tool for overall evaluation of the mission compliance.